INCREASE MUZAKI LOYALTY TO THE ZAKAT, INFAQ, AND SHADAQAH MUHAMMADIYAH INSTITUTIONS IN INDONESIA - Mahdar , Nasrullah (Dinasti Publisher, 2020)
This research aims to prove and analyze the increase in muzaki loyalty through muzaki trust as an intervening variable. The object of this research was the zakat, infaq, and shadaqah Muhammadiyah institutions (LAZISMU) with the analysis unit of Muzaki in DKI Jakarta. The research method used is descriptive and explanatory survey with a minimum sample of 200 respondents, with the data analysis method used was the Structural Equation Model (SEM). The results showed that the quality of service directly had a positive and significant effect on the trust and loyalty of muzaki; muzaki trust has a positive and significant effect on muzaki loyalty; service quality indirectly through muzaki trust has a positive and significant effect on muzaki loyalty; and service quality and muzaki trust simultaneously have a positive and significant effect on muzaki loyalty with a contribution (R2) of 65%. Other findings from this study indicate that muzaki trust is a partial intervening variable on the effect of service quality on muzaki loyalty